Assessing the experience of the quality of care of patients living with multiple sclerosis and their caregivers: The MusiCare questionnaire. (5th January 2021) - Veillard, David; Baumstarck, Karine; Edan, Gilles; Debouverie, Marc; Wiertlewski, Sandrine; De Sèze, Jérôme; Clavelou, Pierre; Pelletier, Jean; Verny, Christophe; Chauvin, Karine; Cosson, Marie Elisabeth; Loundou, Anderson; et al.
Abstract: Background and purpose: Patients with a chronic illness, such as multiple sclerosis (MS), and their natural caregivers have a specific experience of healthcare and health services. These experiences need to be assessed to evaluate the quality of care. Our objective was to develop a French‐language questionnaire to evaluate the quality of care as experienced by MS patients and their natural caregivers. Methods: Eligible patients had been diagnosed with MS according to the McDonald criteria. Eligible caregivers were individuals designated by the patients. The MusiCare questionnaire was developed in two standard phases: (i) item generation, based on interviews with patients and caregivers; and (ii) validation, consisting of validity, reliability, external validity, reproducibility, and responsiveness measures. Results: In total, 1088 patients ( n = 660) and caregivers ( n = 488) were recruited. The initial 64‐item version of MusiCare was administered to a random subsample ( n = 748). The validation process generated a 35‐item questionnaire. Internal consistency and scalability were satisfactory. Testing of the external validity revealed expected associations between MusiCare scores and sociodemographic and clinical data. The questionnaire showed good reproducibility and responsiveness. Conclusions: The availability of a reliable and validated French‐language self‐report questionnaire probing the experience of the quality of care for MS will allow the feedback of patients and caregivers to be incorporated into a continuous healthcare quality‐improvement strategy.